Modeling of the Frictional Behavior at the Contact Surface between the Different Materials Constituting Methane Hydrate Production Well - Masayo KAKUMOTO; Yasuhide SAKAMOTO; Kuniyuki MIYAZAKI; Kazuo AOKI; Akira TAKIGUCHI; Aya YASUI; Jiro MORI (Journal of MMIJ, 2018)
Depressurization process is regarded as the most effective process for gas recovery method from the viewpoints of gas productivity and economic efficiency among in-situ dissociation processes of Methane Hydrate (MH) existing in marine sediments. However, it is supposed that consolidation and deformation of the stratum occurs due to MH dissociation and increase of effective stress in the stratum during operation of depressurization. Consolidation and deformation wreak negative friction on the production well. As a result, the production well may suffer large compressive or tensile stress. In the worst case, it may cause shear failure, tension failure and crushing. Therefore, in order to improve the accuracy for evaluation of stress distribution occurring on production well during depressurization, it is necessary to construct the numerical model enable to reproduce unsteady change of the relationship between shear stress and strain occurring on the contact surface between well and layer and introduce into geo-mechanical simulator. In this study, targeting three contact surface locating above depressurization interval such as 1) casing-cement, 2) casing-layer and 3) cement-layer consisting of different material, we conducted push-out test in laboratory in order to evaluate the frictional behavior at these contact surface based on the relationship between displacement and axial load. From experimental observation, it was found that shear stress occurring on the contact surface linearly increased at the initial stage in the case of steel-cement specimen. On the other hand, for specimens consisting steel-clay and cement-clay, non-linear increase of shear stress was confirmed in the process leading to the shear strength. In addition, shear strength τmax for each contact surface increased depending on effective stress σ ', effective friction angle δ' and effective cohesion c' as failure criteria was estimated based on τmax and σ '. Then, constitutive equation of variable compliance type was applied for reproduction of the relationship between displacement and shear stress observed in a series of push-out test. Through numerical simulation by introduction of this constitutive equation, we confirmed the validity of modeling of the frictional behavior.